Proses Pemilu di Indonesia dari Sudut Pandang Pemantau Asing - Santoso, Topo (UI Scholars Hub, 2021)
Indonesian general election 2004 is the second general election after the fall of Suharto's regime. There have been revolutionary changes on Indonesian general election law and system compare to Indonesian general election that took place during the New Order Regime. Indonesian general election 2004 got very large attention from around the world. Other state were willing to assist in election by providing international observers to closely look at the fairness, impartial process of election have been well achieved. Observation on general election means gather information on the process of election and give opinions based on information on the process of election and give opinion based on information which gathered by people that do not have any authority to intervene on the process. In contrast, Pengawas Pemilu (Indonesian General Election Observer) as a formal body which takes part on general election process has duties to observe, take reports, carry on the reports and settle any disputes. Therefore, Pengawas Pemilu has different functions and authorities compare to others. However, as long as people still do not have any confidence on the process regarding the fairness and neutrality of the general election committee, the role of general election observers is still very important.